Synthesis, characterization, structure and redox property of azo-amido and orthometallated azo-imine platinum(II) complexes. (15th November 2019) - Lal Pratihar, Jahar; Mandal, Paritosh; Lin, Chia-Her
Graphical abstract: Tridentate amido azo and tetradentate orthometallated azo imine platinum(II) complexes were synthesized and structurally characterized. The orthoplatinated complex was formed via oxidative dehydrogenation of one secondary amine group to an imine function, i.e. an intramolecular oxidative rearrangement reaction of the ligand. The deprotonation of the amino group undergoing the oxidative dehydrogenation can be considered as an essential part of the reaction. Abstract: The reaction of the ligands bis-2, 2′-(N-alkylamino)azobenzene, 1a –c, with K2 [PtCl4 ] in a 1:1 ratio in methanol afforded two types of Pt(II) complexes, 2a –b and 2c . Ligands 1a –b give new Pt(II) amido azo complexes, whereas 1c forms an unexpected orthoplatinated azo imine complex through the unusual oxidative dehydrogenation of one secondary amine (–CH2 –NH–) group of the ligand into an imine (–CHN–) function. All three complexes were characterized by 1 H NMR and IR spectroscopy, together with elemental analysis. Furthermore, the solid-state structures of two complexes (2a and 2c ) were determined using single crystal X-ray diffraction analysis. The diffraction analysis revealed that the ligand 1a binds with the Pt(II) ion in a monoanionic terdentate (N, N, N) fashion, offering a distorted square planar geometry where the fourth coordination site is satisfied by one chloride ligand. In contrast, the 1c ligand binds with the Pt(II) ion in a bi-anionic tetradentate (C, N, N, N) fashion, offering a distorted square planar geometry. Several weaker non-covalent forces are responsible for altering the molecular packing in the lattice. The redox properties of the new complexes were also examined.